Investigation of the mechanism of hypertension caused by BTKi in the treatment of hematologic diseases - Jiayi Xu; Junling Lin; Haojian Gan; Qingjian He; WenJuan Wang; Yuanhua Liu (Frontiers in Pharmacology)
Bruton’s tyrosine kinase inhibitors (BTKis) have made substantial impacts on the treatment of B-cell malignancies like chronic lymphocytic leukemia (CLL) and small lymphocytic lymphoma (SLL). Therapeutic benefits aside, the clinical use of BTKis comes with several side effects, of which hypertension (HTN) is quite common and serious and of significant clinical concern. The present article will discuss the mechanisms by which the use of BTKis causes hypertension and outline strategies for managing the condition within the clinic. Studies indicate that using BTKis interferes with BTK’s central role within the B-cell receptor (BCR) signaling cascade and impacts multiple downstream signaling pathways like PI3K/Akt, MAPK, and NF-κB. These changes contribute to endothelial dysfunction, increased oxidative stress, and vascular constriction, all of which are implicated in the development of hypertension. Of special concern is that oxidative stress (OS) is directly related to decreased endothelial nitric oxide (NO) production, a finding that becomes particularly relevant during the initiation of BTKi therapy. Also, BTKis affect vascular development and tone regulation by activating the Notch and RhoA/ROCK pathways, leading to increased vasoconstriction and the advancement of hypertension. In light of the possibility that BTKi-induced hypertension might jeopardize treatment tolerability and patient outcomes, this review proposes a multimodal management of the condition, including careful monitoring of blood pressure, individualized antihypertensive treatment, and possible modifications of the dosing of BTKis. Future investigations should look into the specific molecular mechanisms underpinning the development of hypertension due to BTKis as well as the effects of various antihypertensive regimens on the improvement of the cardiovascular profile of affected individuals.